STRATEGIES TO FOSTER READING INTEREST THROUGH EMERGENT LITERACY AT TAMAN PENGEMBANGAN ANAK MAKARA - Juwitasari, Farah Fida; Laksmi, Laksmi (Edulib, 2019)
This research discusses the strategies to foster reading interest for children at early age at Taman Pengembangan Anak Makara, Universitas Indonesia that is compatible with emergent literacy implemented by effective early childhood teachers. The purpose of this study is to improve the strategy of basic literacy in order to increase reading interest in early childhood in day care centers. This research uses qualitative approach with case study method. The informants were vice coordinators of TPAM, facilitators and co-facilitators, and parents of students. The result shows that the efforts are infusing literacy introduction to children's language development, using interesting media when telling stories, reading books to children before bedtime, teaching children to love books, delivering books creatively and effectively, and providing training to the facilitators in TPAM. It was concluded that emergent literacy in TPAM emphasizes a child-oriented pattern. In essence, children can maximize their potential to have better literacy. The recommendation is that TPAM needs to give more training for the facilitators, add more varied books, and improve books related activities.